Respecting Cultural Differences in Goals of Care Conversations - Choudhury, Divya; Nortjé, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2019)
Goals of care conversations are often tough when patients face a poor prognosis, yet when patients are from a different culture it may be even more difficult. However, seeing cultural values as complementing rather than opposing could be beneficial to the care of the patient.